Pengaruh Perceived Usefullness, Perceived Ease Of Use, dan Subjective Norm Terhadap Purchase Intention Melalui Attitude Sebagai Mediasi (Studi Kasus Pada Konsumen Gudang Digital Online Yogyakarta) - IBN Udayana; Danang Ramadhan (EBBANK, 2019)
This study aims to examine the effect  of Perceived Usefullness, Perceived Ease Of Use, Subjective Norm against Purchase Intention through Attitude. This research was conducted in 100 respondents to Yogyakarta Digital warehouse consumers with respondents who bought digital warehouse products. The results of this study show: 1) Perceived usefullness significant positive effect on Attitude, 2) Perceived Ease Of Use Significant positive effect on Attitude, 3) Subjective Norm significantly positive effect on Attitude, 4) Attitude has not significant positive effect on Purchase Intention, 5) Perceived Usefullness significant positive effect on Purchase Intention, 6) Perceived Ease Of Use significantly positive effect on Purchase Intention, 7) Subjective Norm has not significant positive effect on Purchase Intention